# Combinatorial identity $\sum\limits_{k=0}^{n}\frac{n-k}{k+1}\binom{n}{k}^2 = \binom{2n}{n-1}$

I have an identity $$\sum_{k=0}^{n}\frac{n-k}{k+1}\binom{n}{k}^2 = \binom{2n}{n-1}$$ for which I'm looking for a combinatorial proof. Any ideas?

I was thinking about separating $2n$ on boys and girls, but the fraction that appears on the LHS seems problematic. Dividing by $k+1$ suggests some element being chosen on $k+1$ ways, but I don't see what could be a possible story to that.

One way to deal with the left-hand side is to notice that $$\frac{n-k}{k+1} {n \choose k} = {n \choose k+1} = {n \choose n-1-k}.$$ Therefore the left-hand side is $$\sum_{k=0}^{n-1} {n \choose k}{n \choose n-1-k}.$$ One way to look at this sum is that it counts the number of ways to select a group of size $n-1$ from a population of $n$ girls and $n$ boys. Why? Suppose that we want to count the ways to do this task with the added condition that we choose $k$ girls. So there are ${ n\choose k}$ ways to pick the $k$ (out of $n$) girls and ${n \choose n-1-k}$ ways to pick the remaining $n-1-k$ (out of $n$) boys for the group. Summing over all possible $k$ completes this task.
Now clearly, the number of ways to select a group of size $n-1$ from a population of $2n$ people is ${2n \choose n-1}$.
$\newcommand{\angles}[1]{\left\langle\,{#1}\,\right\rangle} \newcommand{\braces}[1]{\left\lbrace\,{#1}\,\right\rbrace} \newcommand{\bracks}[1]{\left\lbrack\,{#1}\,\right\rbrack} \newcommand{\dd}{\mathrm{d}} \newcommand{\ds}[1]{\displaystyle{#1}} \newcommand{\expo}[1]{\,\mathrm{e}^{#1}\,} \newcommand{\half}{{1 \over 2}} \newcommand{\ic}{\mathrm{i}} \newcommand{\iff}{\Longleftrightarrow} \newcommand{\imp}{\Longrightarrow} \newcommand{\Li}[1]{\,\mathrm{Li}} \newcommand{\ol}[1]{\overline{#1}} \newcommand{\pars}[1]{\left(\,{#1}\,\right)} \newcommand{\partiald}[3][]{\frac{\partial^{#1} #2}{\partial #3^{#1}}} \newcommand{\ul}[1]{\underline{#1}} \newcommand{\root}[2][]{\,\sqrt[#1]{\,{#2}\,}\,} \newcommand{\totald}[3][]{\frac{\mathrm{d}^{#1} #2}{\mathrm{d} #3^{#1}}} \newcommand{\verts}[1]{\left\vert\,{#1}\,\right\vert}$ \begin{align} \color{#f00}{\sum_{k = 0}^{n}{n - k \over k + 1}{n \choose k}^{2}} & = \sum_{k = 0}^{n}{n \choose k}{\color{#f00}{n} \choose \color{#f00}{n - k - 1}} = \sum_{k = 0}^{n}{n \choose k} \oint_{\verts{z} = 1}{\pars{1 + z}^{\color{#f00}{n}} \over z^{\color{#f00}{n - k -1} + 1}}\,{\dd z \over 2\pi\ic} \\[3mm] & = \oint_{\verts{z} = 1}{\pars{1 + z}^{n} \over z^{n}} \sum_{k = 0}^{n}{n \choose k}z^{k}\,{\dd z \over 2\pi\ic} = \oint_{\verts{z} = 1}{\pars{1 + z}^{n} \over z^{n}} \pars{1 + z}^{n}\,{\dd z \over 2\pi\ic} \\[3mm] & = \oint_{\verts{z} = 1}{\pars{1 + z}^{\color{#f00}{2n}} \over z^{\color{#f00}{n - 1} + 1}}\,{\dd z \over 2\pi\ic} = \color{#f00}{2n \choose n - 1} \end{align}